Utopia in performance : finding hope at the theater - Dolan, Jill, 1957- (Book collections on Project MUSE., 2005)
In 'Utopia in Performance', Jill Dolan traces the sense of visceral, emotional and social connection that we experience at the theatre, connections that allow us to feel for a moment not what a better world might look like, but what it might feel like, and how that hopeful utopic sentiment might become motivation for social change.